The sword and the shield: the economics of targeted sanctions - Daniel P. Ahn; Rodney D. Ludema (Center for Economic Studies and ifo Institute (CESifo), 2019)
How effective are “smart” sanctions in imposing costs on an adversary? We consider this question in a model where a targeted regime may choose to “shield” strategically important firms from harm. Using detailed firm and individual data, we estimate the impact on firm performance from smart sanctions deployed by the U.S. and EU against Russia beginning in 2014. We find significant losses in operating revenue, asset values, and employees for sanctioned firms relative to their non-sanctioned peers, which are greater in sectors dependent upon Western service inputs. Strategic firms systemically outperform non-strategic firms under sanctions, implying a cost of shielding to the regime that adds substantially to the total cost of sanctions.
Keywords: F51; 330